A computer vision and smartphone-based tool for onsite color correction and dimensional measurements - Xiong, Wenxi (Nanyang Technological University, 2024)
This project aims to develop a portable and low-cost solution which is capable of accurately measuring objects in 3-dimensional (3D) space and providing on-site color correction functionality under varying lighting conditions. The solution leverages advanced measurement, computer vision, and cloud computing technologies to modernize traditional dimensional measurement and color correction practices.